2016
DOI: 10.1016/j.tranon.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Whole Brain Radiotherapy and RRx-001: Two Partial Responses in Radioresistant Melanoma Brain Metastases from a Phase I/II Clinical Trial

Abstract: BACKGROUND: Kim et al. report two patients with melanoma metastases to the brain that responded to treatment with RRx-001 and whole brain radiotherapy (WBRT) without neurologic or systemic toxicity in the context of a phase I/II clinical trial. RRx-001 is an reactive oxygen and reactive nitrogen species (ROS/RNS)-dependent systemically nontoxic hypoxic cell radiosensitizer with vascular normalizing properties under investigation in patients with various solid tumors including those with brain metastases. SIGNI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…After intravenous infusion, RRx-001 binds to red blood cells, circulates systemically, adheres to aberrant tumour vessels whereby RRx-001 bound red blood cells are activated within hypoxic tumour regions to release RRx-001 and its metabolites into the tumour microenvironment. Via red-blood cell delivery, RRx-001 has been shown to cross the blood-brain barrier (BBB), and reach hypoxic tumours inside the brain [8,10]. Both preclinical and clinical studies have shown that RRx-001 penetrates into hypoxic tumours, resulting in central tumour necrosis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…After intravenous infusion, RRx-001 binds to red blood cells, circulates systemically, adheres to aberrant tumour vessels whereby RRx-001 bound red blood cells are activated within hypoxic tumour regions to release RRx-001 and its metabolites into the tumour microenvironment. Via red-blood cell delivery, RRx-001 has been shown to cross the blood-brain barrier (BBB), and reach hypoxic tumours inside the brain [8,10]. Both preclinical and clinical studies have shown that RRx-001 penetrates into hypoxic tumours, resulting in central tumour necrosis [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Like bevacizumab and the RTK inhibitors, the experimental, pan-epigenetic and tumor-associated myeloid repolarizing agent, RRx-001 102 has also been associated with normalization of the tumor vasculature, although, admittedly, this non-VEGF-related property may be attributable to the unique mechanism of RRx-001 rather than a general class effect of epigenetic agents. 103 However, as a class, epigenetic therapies have the potential to reverse hypoxia-induced silencing of tumor suppressor and other beneficial genes with or without vascular normalizing agents.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of using predicted risks and Bayesian models to estimate anticipated toxicity at given time points can be using to accelerate trial recruitment in a safe and robust manner [35]. Of particular interest is the time-toevent continual reassessment method [36], a methodology that has been used in clinical trials of novel radiotherapy-drug combinations in other disease settings [37] and is increasingly viewed as the most appropriate study design in this research field.…”
Section: Introductionmentioning
confidence: 99%